Werkpolitik in der Antike Studien zu Cicero, Vergil, Horaz und Ovid - Scheidegger Lämmle, Cédric (Zetemata, 2016)
Of the various forms of collecting and cataloguing literary texts, classification as part of an authorial œuvre is one of the most common. The notion of the œuvre is often legitimised with regard to seemingly objective criteria, such as the extent or chronology of an author's production, and its implications are thus downplayed and glossed over. By contrast, the present study explores the specific preconditions (and repercussions) of privileged status accorded to the idea of the authorial corpus. It argues that Late Republican and Augustan Latin literature is an especially momentous time in the history of the literary œuvre. The significant changes in literary culture that this period witnessed, not least the establishment of public libraries in Rome, led to an increasing awareness of and attention to the formation of textual corpora among literary practitioners, critics and readers, which has in turn had a formative influence on the idea of the authorial corpus. In four case studies, on Cicero, Virgil, Horace, and Ovid, the book highlights the different ways in which the œuvre is envisaged and formed, both within the literary works themselves and in their reception.